HOW TO ENFORCE CRIMINAL LAW AGAINST NARCOTICS ABUSE OF NEW TYPES OF VARIANTS THAT HAVE NOT BEEN INCLUDED IN LAW NUMBER 35 OF 2009 CONCERNING NARCOTICS - Lukas Pardamean E. Marbun; Hedwig; Mohamad Ismed (Transpublika Publisher, 2023)
Today, many different narcotics, psychotropics, and other illegal drugs emerged. These new variants are not/have not been regulated by law number 35 of 2009 concerning narcotics. This research uses Normative Juridical methodology. The data used for the formulation of the problem is secondary data consisting of primary, secondary and tertiary legal documents. The results of the analysis show that in order to implement the provisions of Article 6 paragraph (3) of the Narcotics Law, it is necessary to stipulate a Regulation of the Minister of Health concerning Changes in the Classification of Narcotics, which is the last position where this research was written. Minister of Health of the Republic of Indonesia Number 4 of 2021 concerning changes to the classification of narcotics. Law Number 35 of 2009 concerning Narcotics and Regulation of the Minister of Health of the Republic of Indonesia Number 4 of 2021 concerning changes to the classification of narcotics which are guidelines for law enforcement against drug abuse with new variants in Indonesia are still deemed ineffective and efficient and do not accommodate all needs -the need for law enforcement against narcotics abuse, especially narcotics with new types of variants. An alternative policy formulation to Law Number 35 of 2009 concerning Narcotics, the formulation policy that is deemed suitable for implementation in the future is to revise Law Number 35 of 2009 concerning Narcotics in particular to expand the meaning related to narcotics in the provisions of Article 1 number 1 and/or Article 6 paragraph (1).